Vital Signs: Sodium Intake Among U.S. School-Aged Children — 2009–2010 - Cogswell, Mary E. (MMWR Morb Mortal Wkly Rep, 2014)
BACKGROUND: A national health objective is to reduce average U.S. sodium intake to 2,300 mg daily to help prevent high blood pressure, a major cause of heart disease and stroke. Identifying common contributors to sodium intake among children can help reduction efforts. METHODS: Average sodium intake, sodium consumed per calorie, and proportions of sodium from food categories, place obtained, and eating occasion were estimated among 2,266 school-aged (6–18 years) participants in What We Eat in America, the dietary intake component of the National Health and Nutrition Examination Survey, 2009–2010. RESULTS: U.S. school-aged children consumed an estimated 3,279 mg of sodium daily with the highest total intake (3,672 mg/d) and intake per 1,000 kcal (1,681 mg) among high school–aged children. Forty-three percent of sodium came from 10 food categories: pizza, bread and rolls, cold cuts/cured meats, savory snacks, sandwiches, cheese, chicken patties/nuggets/tenders, pasta mixed dishes, Mexican mixed dishes, and soups. Sixty-five percent of sodium intake came from store foods, 13% from fast food/pizza restaurants, 5% from other restaurants, and 9% from school cafeteria foods. Among children aged 14–18 years, 16% of total sodium intake came from fast food/pizza restaurants versus 11% among those aged 6–10 years or 11–13 years (p<0.05). Among children who consumed a school meal on the day assessed, 26% of sodium intake came from school cafeteria foods. Thirty-nine percent of sodium was consumed at dinner, followed by lunch (29%), snacks (16%), and breakfast (15%). IMPLICATIONS FOR PUBLIC HEALTH PRACTICE: Sodium intake among school-aged children is much higher than recommended. Multiple food categories, venues, meals, and snacks contribute to sodium intake among school-aged children supporting the importance of populationwide strategies to reduce sodium intake. New national nutrition standards are projected to reduce the sodium content of school meals by approximately 25%–50% by 2022. Based on this analysis, if there is no replacement from other sources, sodium intake among U.S. school-aged children will be reduced by an average of about 75–150 mg per day and about 220–440 mg on days children consume school meals.